Systems of distributed artificial intelligence for analysis of oil product transportation processes: evidence from Russia. (23rd March 2022) - Serova, Elena; Shklyaev, Daniil
At present, the use of artificial intelligence (AI) methods and tools is an essential component of management information systems for a company to succeed in a rapidly changing environment. Agent-based modelling systems as systems of distributed AI must be considered nowadays as an obligatory stage of decision-making in Russian oil and gas companies, which use modern information technologies actively. The paper is focused on the description and comparative analysis of system dynamics and agent-based modelling, used for intelligent decision support systems development in transport logistics. The main goal of this research is evaluation of the multi-agent system's role for decision-making processes and management information systems development and creating the model of logistics processes (the processes of oil and oil products transportation, loading, and unloading). The work is based on a generalisation of theoretical researches in this area along with international practices and domestic experience.